Exploring Limited Capacity in the Grid: Actors, Problems, and Solutions - Palm, Jenny (Frontiers in Energy Research, 2021)
An extensive and reliable electricity grid is essential for all sectors of society. In parts of Sweden, the electricity grid has been suffering from a lack of capacity. This is something affecting all sectors and all people in these regions. The capacity problems have however so far mainly been analyzed in a technical system perspective, focusing on incumbent actors, whereas other actors have been less researched. This article aims to fill this gap and include a variety of Swedish actors’ perceptions on the lack of electricity grid capacity. It is, however, a challenge to capture the views of others than the professionals working in the area because the electricity grid in not something people, in general, reflects upon. The article takes an explorative approach to the subject by analyzing problems and solutions raised in four arenas: the regulative, media, technocratic, and user. It also focuses on the city of Malmö in Sweden and two projects where the lack of grid capacity has been discussed. Sweden’s lack of capacity concerns that although electricity is available, the energy grid cannot transmit the required amount of electricity to all parts of the country. The article concludes that the electricity grid has been developed within a technocratic frame, with a few professionals dominating the agenda, which has led to a convergence of perspectives and narrowing options. In the regulative arena, which often decides what issues are prioritized and in the end implemented, there is a focus on investment in transformers and lines rather than demand-side solutions and user flexibility. Technological and economical values are dominating all arenas and other values such as user engagement and ownership are marginalized.